Bisexuality among a cohort of university students: prevalence and psychological distress. Issue 2 (April 2018) - Ciocca, Giacomo; Solano, Caterina; Di Lorenzo, Giorgio; Limoncin, Erika; Mollaioli, Daniele; Carosa, Eleonora; Collazzoni, Alberto; Santarnecchi, Emiliano; Bianciardi, Emanuela; Niolu, Cinzia; Siracusano, Alberto; Rossi, Alessandro; et al.
Abstract Sociocultural prejudices and pressures may impair the mental health of bisexual people. We aim to evaluate psychological status according to sexual orientation in a sample of Italian university students, with specific attention to bisexuality and its frequency. Among a recruited sample of 551 university students, we found the following percentages for sexual orientation: heterosexuals 96.9% (n = 534), homosexuals 1.1% (n = 6), bisexuals 2% (n = 11). The cross-sectional analysis for psychological symptoms, with the Symptoms Check List-90 Revised (SCL-90-R), revealed that bisexual subjects have statistically significant higher scores on some symptomatic scales compared to heterosexuals. In particular, obsession-compulsion, paranoid ideation, hostility were significantly higher in bisexuals. Therefore, if heterosexual or homosexual orientation are not specified by particular psychological symptoms, bisexuality is characterized by a strong link with some facets of psychological distress, which are likely caused by a peculiar double stigma. In conclusion, through a specific psychometric tool, we found an association between bisexuality and various forms of psychological suffering. This evidence should further encourage clinicians to accurately assess the psychological health in young bisexual people.